Customer Satisfaction with Texas Collection Bag Purchase Decision at Texas Collection Store East Jakarta - Arum Fitri Nuryanti; Resti Hardini; Kumba Digdowiseiso (Syntax Corporation Indonesia, 2023)
This study aims to determine the effect of the t-test on product quality, word of mouth and customer satisfaction on purchasing decisions for Texas Collection bags at Texas Collection stores, East Jakarta. Sources of data This study uses primary data in the form of a questionnaire, the data of this study was given to 97 respondents who made purchasing decisions Texas Collection East Jakarta. The data analysis technique used was multiple linear regression and hypothesis testing using t-statistics that had been processed by SPSS 26. The results showed that product quality (X1) positively and significantly influenced purchasing decisions. This can be seen from the results of the t-test where tcount (2.814 > 1.984). The Word of Mouth (X2) variable has a positive and significant influence on purchasing decisions. This can be seen from the results of the t-test where tcount (5.377 > 1.984). Customer Satisfaction Variable (X3) has a positive and significant influence on purchasing decisions. This can be seen from the results of the t test where tcount (0.018 < 0.05).